Growth of Mungbean (Vigna radiata L.) in Salinity Stress Condition With Additional Biostimulan of Gotu Kola Extracts (Centella asiatica (L.) Urban.) - Desika Saputri; Zulfa Zakiah; Mukarlina Mukarlina (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Mungbean (Vigna radiata L.) is a palawija plant that is widely cultivated in Indonesia and includes glycophyte plants that are sensitive to salinity. Salinity stress can affect changes in morphological characters and growth in plants. The addition of gotu kola extract biostimulants can be a solution to reduce the effect of salinity stress on plants. This study aims to determine the effect and concentration of gotu kola extract biostimulant on the morphological and growth characteristics of mungbean plants experiencing salinity stress. This study used a completely randomized design (CRD) with 2 factors, namely NaCl concentration consisting of controls A1 (0‰), A2 (1.6‰), A3 (3.2‰), A4 (4.8‰) and A5 (6.4‰) as well as the concentration of biostimulants consisting of controls B1 (0mg/L), B2 (12.5mg/L), B3 (25mg/L), B4 (50mg/L) and B5 (100mg/L). Data were analyzed using ANOVA and continued with Duncan’s Multi Range Test with a 95% level of confidence. The results showed that the combination treatment of NaCl and gotu kola extract biostimulants had a significant effect on shoot fresh weight (grams), total fresh weight (grams), shoot dry weight (grams), total dry weight (grams), but had no significant effect on mungbean height. (cm), number of leaves (stalk), leaf area (cm2), root fresh weight (grams) and root dry weight (grams). Combination treatment of 3.2‰ NaCl and 25 mg/L biostimulant was the treatment that produced the best shoot dry weight and dry weight from the growth of mungbean plants experiencing salinity stress.